Ubiquitous Personality‐Trait Concepts in 13 Diverse and Isolated Languages: A Cluster–Classification Approach. Issue 2 (3rd March 2020) - Wood, Joshua K.; Gurven, Michael; Goldberg, Lewis R.
Abstract: There is longstanding interest in the generalizability of personality across diverse cultures. To investigate the generalizability of personality concepts, we examined the English translations of individual‐difference entries from the dictionaries of 12 small‐scale societies previously studied for ubiquity of individual differences plus the dictionary of an additional society not previously studied in this manner. These 13 societies are highly diverse in geographical location, culture, and language family; their languages developed in isolation from modern‐world languages. The goal of our exploratory research was to discover ubiquitous personality concepts in these 13 independent societies and their languages, providing a window into personality concepts across a broad range of cultures and languages. This study used clusters of empirically related terms (e.g. brave, courageous, and daring), based on a taxonomy of English‐language personality concepts that consisted of 100 personality‐trait clusters. English‐language definitions of dictionary entries from the 13 languages were matched to the meanings of the synonym clusters. The cluster–classification method uncovered nine ubiquitous personality concepts, plus six that were present in at least 12 of the 13 languages. The nine ubiquitous personality concepts include some not previously identified and suggest a core of possibly universal concepts. © 2020 European Association of Personality Psychology